Cavity ringdown spectroscopy for broadband and microfluidics applications - Oag, R (2011)
Cavity Ringdown Spectroscopy (CRDS) is a highly sensitive, absorption spectroscopy technique. From the measurement of the decay of light within an optical cavity, spectroscopic parameters of an absorbing sample can be determined. Thus far the technique has mostly been applied to gas-phase samples. The work described in this thesis attempts to extend the technique to the condensed phase. A supercontinuum source and streak camera detector were used to enable broadband measurements (~ 500 – 600 nm) of the absorption spectra of gaseous NO2 and I2 samples. The setup had a detection sensitivity of 20 ± 7 ppm, and was capable of making an accurate measurement of the wavelength-dependent reflectivity of the cavity mirrors. Microfluidic devices have been employed in a range of fields for purposes including small volume organic synthesis, environmental monitoring and medical diagnosis. They enabled us to make measurements on condensed phase samples by integrating a ‘test’ microfluidic chip into a single wavelength CRDS setup and flowing liquid through its channels. Using a series of rhodamine 6G solutions the detection sensitivity of our setup was determined to be (4.2 ± 0.3) x 10-6 M, with a sample volume of 12.3 nL. The technique was also used to measure the titration curve of phenolphthalein prepared in a series of buffer solutions with pHs ranging from 7.7 to 11.0, and was capable of determining the pH of nanolitre samples to an accuracy of ± 0.028. In the final set of measurements reported here, the technique was used to follow the kinetics of the iodine clock reaction. The results showed good agreement with bulk measurements made using a single-pass spectroscopic technique.